Enhancing MSME Competence through Managing Finances Training in Waena Village, Jayapura City - Meinarni Asnawi; Paulus K. Allo Layuk; Alfiana Anto; Rizka A. Nurjannah; Maria A. Patty (International Journal Of Community Service, 2025)
This community service program on Financial Management for MSMEs aims to strengthen local micro, small, and medium enterprises (MSMEs) in Jayapura by improving their ability to manage finances and sustain their businesses. The program addresses key issues such as low financial literacy, limited access to capital, lack of competitiveness, and the need for stronger collaboration between academia and MSMEs.Training focused on practical financial management skills, including cash flow, receivables, budgeting, and working capital. It also introduced basic business financing and strategies for managing financial emergencies. The program was delivered through face-to-face sessions combining lectures, discussions, and simulation games.A total of 29 MSME participants from various business sectors took part in the training. Evaluation results showed an improvement in participants’ understanding and ability to manage their business finances. This program demonstrates the potential of targeted financial literacy initiatives to enhance the resilience and competitiveness of MSMEs, enabling them to better support their families and contribute to local economic development.